2019
DOI: 10.1016/j.nicl.2019.102063
|View full text |Cite
|
Sign up to set email alerts
|

Bias-adjustment in neuroimaging-based brain age frameworks: A robust scheme

Abstract: HighlightsWe present a robust and simple bias-adjustment scheme for neuroimaging-based brain age frameworks.The efficiency of proposed bias-adjustment scheme was assessed in the context of cognitively healthy aging and Alzheimer's disease.The proposed bias-adjustment scheme was shown efficient and statistically improved results, making it a necessary part for future brain age frameworks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
148
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 145 publications
(155 citation statements)
references
References 20 publications
7
148
0
Order By: Relevance
“…To mitigate the residuals' dependence on age, researchers apply the following algorithm (Beheshti et al, 2019;Smith et al, 2019;Liang et al, 2019;Chung et al, 2018) Then, for a left out subject i with brain data B i1 , B i2 , . .…”
Section: Risks Of Using a Modified Brain Age Gapmentioning
confidence: 99%
See 4 more Smart Citations
“…To mitigate the residuals' dependence on age, researchers apply the following algorithm (Beheshti et al, 2019;Smith et al, 2019;Liang et al, 2019;Chung et al, 2018) Then, for a left out subject i with brain data B i1 , B i2 , . .…”
Section: Risks Of Using a Modified Brain Age Gapmentioning
confidence: 99%
“…(7). If Beheshti et al (2019) implemented their method as stated, they would have found that the correlation after their adjustment dramatically underestimates of the true correlation (see Figure 2). To illustrate what correlation would be obtained if the reported transformations were used, correlations using both the transformation and the equivalent function are plotted.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 3 more Smart Citations